Child–Computer Interaction at the Beginner Stage of Music Learning: Effects of Reflexive Interaction on Children’s Musical Improvisation - Addessi, Anna Rita; Anelli, Filomena; Benghi, Diber; Friberg, Anders (Frontiers in Psychology, 2017)
In this article children’s musical improvisation is investigated through the “reflexive interaction” paradigm. We used a particular IRMS, the MIROR-Impro, implemented in the MIROR project (EC-FP7), which is able to reply to the child playing a keyboard by a “reflexive” output, mirroring (with repetitions and variations) her/his inputs. The study was conducted in a public primary school, with 47 children, aged 6 to 7. The experimental design used the convergence procedure, based on three sample groups allowing us to verify if the reflexive interaction using the MIROR-Impro is necessary and/or sufficient to improve the children's abilities to improvise. The following conditions were used as independent variables: to play only the keyboard, the keyboard with the MIROR-Impro but with not-reflexive reply, the keyboard with the MIROR-Impro with reflexive reply. As dependent variables we estimated the children’s ability to improvise in solos, and in duets. Each child carried out a training program consisting of 5 weekly individual 12 minute sessions. The control group played the complete package of independent variables; exp. group 1 played the keyboard and the keyboard with the MIROR-Impro with not-reflexive reply; exp. group 2 played only the keyboard with the reflexive system. One week after, the children were asked to improvise a musical piece on the keyboard alone (Solo task), and in pairs with a friend (Duet task). Three independent judges assessed the Solo and the Duet tasks by means of a grid based on the TAI-Test for Ability to Improvise rating scale. The EG2, which trained only with the reflexive system, reached the highest average results and the difference with EG1, which did not used the reflexive system, is statistically significant when the children improvise in a duet. The results indicate that in the sample of participants the reflexive interaction alone could be sufficient to increase the improvisational skills, and necessary when they improvise in duets. However, these results are in general not statistically significant. The correlation between Reflexive Interaction and the ability to improvise is statistically significant. The results are discussed on the light of the recent literature in neuroscience and music education.